The normal kid - Holmes, Elizabeth Ann, 1957- (Carolrhoda Books, 2012)
Told in their separate voices, fifth-graders Sylvan, whose parents' divorce causes him stress, and Charity, who lived in Kenya for the past five years, both strive for normalcy at school and start a petition to keep their teacher, Mr. In, from being fired.